Studi Evaluasi Mekanisme Hand Rub (Hand Sanitizer) Berbasis Alkohol Terhadap Methicillin-Resistant Staphylococcus Aureus (MRSA) Dengan Metode Pengamatan Scanning Electron Microscope (SEM) - Subhan, Ahmad (RSUP Fatmawati, 2022)
The current pandemic caused by the current Corona Virus Infection Disease (Covid 19), as well as those caused by Methicillin-resistant Staphylococcus aureus (MRSA) clones in the previous period, have seriously threatened human life. These conditions require materials that can break the chain of transmission from human to human and the environment to human. Alcohol-based hand rubs/hand sanitizers are widely used, generally containing ethanol, isopropanol or n-propanol, or a combination of the two types. Alcohol has excellent germicidal activity in vitro against gram-positive and gram-negative vegetative bacteria (including multidrug-resistant pathogens such as MRSA and VRE) as well as against viruses. This study aimed to determine the effect of alcohol-based hand rub (hand sanitizer) on Methicillin-resistant staphylococcus aureus (MRSA) using the scanning electron microscope (SEM) observation method. The hand rub product used in this study is a modified version of the WHO standard formula, which is the best formula based on formulation stability tests in previous studies. Methicillin-resistant staphylococcus aureus (MRSA) used in this study was the result of swab wounds of patients undergoing treatment at the research hospital. The SEM examination was carried out at the Indonesian Institute of Sciences (LIPI) Serpong using the SEM JSM IT200. The results showed that at 5,000X magnification, it was seen that MRSA underwent a lysisin colony at each of the cell wall structure with the occurrence of colony deformation which caused the separation of each cell from the main colony. At 10,000X magnification, Methicillin-resistant Staphylococcus aureus (MRSA) colonies appeared to be lysed in the cell wall structure with deformation and coagulation in the main colonies of MRSA cells. In 10,000X observations of single cells showed a lysis of the MRSA cell wall structure and it damage the structures surrounding the cell, which caused cell death. Keywords: hand rub, alcohol base, IFO, Ahmad, Subhan, fatmawati, MRSA, SEM